Excess mortality during the COVID-19 pandemic: a case study of Oxfordshire - Reshania, N (2020)
Background: Determination of excess mortality provides a useful measure of demonstrating the true toll of the COVID-19 pandemic by capturing both the direct and indirect causes of death. This study estimates the weekly trend in excess mortality over the first 28 weeks of 2020 in Oxfordshire and its five districts, ascertaining the contribution of COVID-19 to the observed excess mortality. This is further complemented by a review of local hospital utilisation and mortality data to understand the collateral damage of the pandemic.